A Concentrated Review of Current Developments in the Diagnosis and Treatment of Viral Mumps - Mohammed Nadeem Khan; Ashok Kumar; Praveen Chandra Dubey (International Journal of Tropical Medicines, 2024)
Viral mumps, caused by the mumps virus, continues to pose public health challenges globally despite the availability of vaccines. Considerable advancements have been achieved in the last few years about the pathophysiology, diagnosis, and management of viral mumps. This focused review aims to highlight the latest advances in the diagnosis and treatment of viral mumps, with a particular emphasis on innovative strategies and emerging therapies. Key topics covered include the evolution of diagnostic techniques such as molecular assays and serological tests, novel biomarkers for disease detection and monitoring, advances in antiviral therapies and supportive care, including the use of antiviral medications and immunomodulatory agents. Additionally, we discuss challenges in diagnosis, management, and prevention of viral mumps, including vaccine hesitancy and outbreaks in various populations. By summarizing recent developments, this review provides clinicians and researchers with valuable insights into optimizing the diagnosis and management of viral mumps, ultimately contributing to improved patient outcomes and the control of mumps outbreaks
Keywords: Biomarkers; Viral mumps; antiviral therapy; diagnosis; immunomodulatory agents; mumps virus; outbreaks; treatment; vaccine hesitancy